A study on the factors that contribute the customer-supplier relationship. A case study of Giffarine Skyline Unity (M) Sdn. Bhd / Noor Amira Ab Rahman - Ab Rahman, Noor Amira (2011)
This study determines the factors that contribute to the customer-supplier relationship, a case of Giffarine Skyline Unity(M)Sdn. Bhd. The independent variables are trust, communication, power-dependent and cooperation. The objectives of this study are to identify the factors that contribute to customer-supplier relationship and to identify the impact of customer-supplier relationship on company success. This study is conducted at Giffarine’s branches and involved 100 respondents. The findings of this research are analyzed and interpreted using frequencies tables, reliability and correlation. The results show that all the independent variables have significant effects toward the customer-supplier relationship at Giffarine. Based from the results obtained, several recommendations are suggested that can help Giffarine to improve its relationship with the customer